A range for the "real" value of internal mechanical power in cycling - Giorgi, H.; Andrews, M.; Gray, A.; Osborne, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: A number of complex frameworks have been developed for considering metabolic energy supply and various energy demands during cycling. None of these, however, adequately account for the cost of moving the limbs against inertial and gravitational forces, i.e., the internal mechanical power (IP). Previously, IP has been determined using either a physiological or a biomechanical approach. The physiological approach is valuable because it quantifies the energy state of the entire system where changes to whole-body energy metabolism with changes in energy demands are relatively indisputable. This approach, however, generally determines IP by subtracting external mechanical power (EP), the power applied externally on the pedals, and the metabolic cost of rest from the total energy expenditure. This simple relationship has been rebuked by biomechanists, who have instead argued that there is some degree of energy transfer from IP to EP, i.e., they do not have independent metabolic costs. The biomechanical approach can determine the potential and kinetic energies of the separate body segments and can largely distinguish the muscle groups from which the energy was sourced. The greatest limitation to this approach, however, is that it does not account for the dissipation of energy to heat, a significant destination of metabolic energy in the human body. The purpose of this study was to consider the approaches together to calculate a range of values for IP during cycling at 200 W and 80 and 110 rev/min. Methods: Ten elite cyclists completed five-minute bouts of cycling at 0 W (no chain attached) and 200 W, at 80 and 110 rev/min. Oxygen consumption during unloaded cycling was converted to metabolic power and then transformed to its mechanical counterpart by multiplying by delta efficiency. This represented the physiological estimate of IP. The biomechanical estimate of IP at 200 W was taken as the summed muscle joint powers, determined from inverse dynamics analysis, in excess of that required to apply power to the pedals. Results: The range of IP estimates at 80 rev/min was constrained at the lower limit by the biomechanical estimate of 28 ± 11 W and at the upper limit by physiological estimate of 56 ± 9 W. At 110 rev/min, the biomechanical estimate was 34 ± 17 W and the physiological estimate was 96 ± 13 W. Discussion: The proposal for a range of values for IP is novel and represents a more comprehensive description of the flow of metabolic to mechanical energy than when only one approach is used. Future efforts to refine the models that predict the upper and lower limits should see these limits move closer together and toward the real value of IP. Such an improvement may have implications for improved cycling performance predictions.